2018
DOI: 10.1002/slct.201802374
|View full text |Cite
|
Sign up to set email alerts
|

The Calotropis procera Transformed Green NiO and Fe‐NiO Nanoparticles for Diaryl Pyrimidinones Synthesis in Hydrotropic Medium at Room Temperature

Abstract: We report the synthesis of NiO and Fe doped NiO nanoparticles by simple and cost effective Calotropis procera leaf extract assisted green co‐precipitation method. The leaf extract of Calotropis procera acts as reducing as well as capping agent for the synthesis of NiO and Fe doped NiO. The presence of –OH and aldehydic group (‐CHO) on synthesized nanoparticle imparts their strong interaction with synthesized nanoparticles, conveying efficient catalyst for heterocycle synthesis. The proficient catalytic applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…(i) Homogeneous 16,21 (i) Homogeneous 26 or (i) Heterogeneous 39 (i) Truly heterogeneous 109 (ii) Heterogeneous 9,39 (ii) Heterogeneous 39 3. Aggregation of catalyst Observed 20 Observed 48 Less 83 Very less 105,117…”
Section: Catalyst In Reaction Mediummentioning
confidence: 98%
See 1 more Smart Citation
“…(i) Homogeneous 16,21 (i) Homogeneous 26 or (i) Heterogeneous 39 (i) Truly heterogeneous 109 (ii) Heterogeneous 9,39 (ii) Heterogeneous 39 3. Aggregation of catalyst Observed 20 Observed 48 Less 83 Very less 105,117…”
Section: Catalyst In Reaction Mediummentioning
confidence: 98%
“…However, the authors observed better reaction results with the Fe@NiO NPs than the NiO NPs for the synthesis of pyrimidinone derivatives. 83 After the successful synthesis of Fe-doped NiO NPs, Shinde et al synthesized Ni@ZnO NPs and used them as a catalyst for the synthesis of 3,4-dihydropyrimidin-2(1 H )-ones [Scheme 28] in water with the NaPTS hydrotrope. 84 In these environmentally conscious times, researchers are required to focus on developing green methodologies for organic transformations.…”
Section: Bimetallic Npsmentioning
confidence: 99%